Gravitational Attraction Fields for Population in Turkey - Cihan Ahmet Tutluoğlu; Vedia Dökmeci (European Regional Science Association (ERSA), 2005)
Inspired by the gravitational attraction of the masses in Physics, the gravitational pull between the settlements has been proven to be an important phenomenon in explaining potentials that arise among towns. Again inspired by the Electro-magnetic fields in Physics, in this paper, the gravitational attraction between the cities is assumed to be exerted on a city with a certain "charge” on a map of superimposing "charges” of different cities. Following this line, an attraction field has been presented for different census years on city basis in Turkey and possible implications have been evaluated. The values for the year 2000 on the other hand have been tested with other factors including the GNP per head, population and the literacy rate to see the impact of these forces on the tendencies to move in and out of the cities, that is the migrationary effects. The study is as well done seperating the country into a West and an East to see if there are striking differences in between.
Keywords: 330